2022
DOI: 10.1021/acschembio.1c00882
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions between a Membrane Protein and a Glycolipid Essential for Membrane Protein Integration

Abstract: Inducing newly synthesized proteins to appropriate locations is an indispensable biological function in every organism. Integration of proteins into biomembranes in Escherichia coli is mediated by proteinaceous factors, such as Sec translocons and an insertase YidC. Additionally, a glycolipid named MPIase (membrane protein integrase), composed of a long sugar chain and pyrophospholipid, was proven essential for membrane protein integration. We reported that a synthesized minimal unit of MPIase possessing only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…S11 ). In a previous study, we observed that the interaction rate between mini-MPIase and Pf3 coat protein were accelerated when mini-MPIase-3 was reconstructed in DAG-containing EPL LUVs, suggesting that it assembles on the membrane cooperatively 18 . We also observed that mini-MPIase-3 electrostatically interacts with DAG on the membranes and inhibited the flip-flop motion of DAG 21 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…S11 ). In a previous study, we observed that the interaction rate between mini-MPIase and Pf3 coat protein were accelerated when mini-MPIase-3 was reconstructed in DAG-containing EPL LUVs, suggesting that it assembles on the membrane cooperatively 18 . We also observed that mini-MPIase-3 electrostatically interacts with DAG on the membranes and inhibited the flip-flop motion of DAG 21 .…”
Section: Discussionmentioning
confidence: 90%
“…Recently, we demonstrated the importance of a pyrophosphate linker in MPIase for affinity with Pf3 coat protein in an aqueous environment by surface plasmon resonance (SPR) analyses and docking simulations 18 . These results suggest that the pyrophosphate linker of MPIase is one of the key structures in membrane insertion activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] DS studies deduced that the GlcNAc 6-OAc and NHAc groups interact with the hydrophobic amino acid residues of the substrate protein, and that pyrophosphate and uronate interact electrostatically with basic amino acids. [15] In this study, the importance of the GlcNAc 6-OAc and carboxy groups was experimentally proven using trisaccharide analogs. Since the effect of individual functional groups was weak, alteration of one functional group did not completely abolish activity.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%